Safety Evaluation of Large-size Transportation Bridges Based on Combination Weighting Fuzzy Comprehensive Evaluation Method. Issue 1 (June 2021) - Liu, Hua; Li, Bin; Sun, Yiqi; Dou, Xiaozheng; Zhang, Yongfu; Fan, Xianghui
Abstract: The load of large-size vehicles has not been clearly defined in the existing bridge design codes in our country. When large-size vehicles cross the bridge, the bridge has certain safe-ty hazards. At present, there are not many evaluation methods for the driving safety of large-size transportation bridge structures. In order to scientifically evaluate the traffic safety of the large-size transportation bridge structure, this paper considers the factors of bridge, traffic and environment, and establishes the evaluation index system for the operation safety of the large-size transportation bridge structure, using the comprehensive weighting method of the G1-entropy weight method. Calculating the weight and combining the fuzzy comprehensive evaluation method to evaluate the traffic of the large-scale transportation bridge in Huanglong County, Shaanxi Province, the results show that the traffic safety level of the bridge is level II, which has good safety.